Subtraction diagnosis in sunflower - Cruz, Mara Cristina Pessoa da; Ferreira, Manoel Evaristo; Fernandes, Nelson Gimenes (Pesquisa Agropecuaria Brasileira, 2014)
Looking for the probable causes of the appearance of abnormalities in a sunflower crop (Helianthus annuus once the possibilite of a parasitic disease had been eliminated, a diagnostic test was done by subtraction, wherein the plant nutrients N, K, S, B, Mo, Cu, Mn and Zn were omitted. A sandy-phase dark-red latosol from the farm where the problem had been observed was used. In the -N, -K, -S and -B treatments deficiency symptoms appeared in which (except for -S treatment) also a significant reduction in the total dry water weight occurred, as related to the complete treatment. Those symptoms did not match the field deficiency symptoms. However, it is postulated that the cause of the symptoms observed in the field may lie in the interaction among these four nutrients.